Moxifloxacin and Sulfamethoxazole-Based Nanocarriers Exhibit Potent Antibacterial Activities - Noor Akbar; Jasra Gul; Ruqaiyyah Siddiqui; Muhammad Raza Shah; Naveed Ahmed Khan (MDPI AG, 2021)
Antibiotic resistance is a major concern given the rapid emergence of multiple-drug-resistant bacteria compared to the discovery of novel antibacterials. An alternative strategy is enhancing the existing available drugs. Nanomedicine has emerged as an exciting area of research, showing promise in the enhanced development of existing antimicrobials. Herein, we synthesized nanocarriers and loaded these with available clinically approved drugs, namely Moxifloxacin and Sulfamethoxazole. Bactericidal activity against Gram-negative (Serratia marcescens, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Salmonella enterica) and Gram-positive (methicillin-resistant Staphylococcus aureus, Streptococcus pneumoniae, and Bacillus cereus) bacteria was investigated. To characterize the nanocarriers and their drug-loaded forms, Fourier-transform infrared spectroscopy, dynamic light scattering, and atomic force microscopy were utilized. Antibacterial assays and hemolysis assays were carried out. Moreover, lactate dehydrogenase assays were performed to determine cytotoxicity against human cells. The results depicted the successful formation of drug-nanocarrier complexes. The potent antibacterial activities of the drug-loaded nanocarriers were observed and were significantly enhanced in comparison to the drugs alone. Hemolysis and cytotoxicity assays revealed minimal or negligible cytotoxic effects against human red blood cells and human cells. Overall, metronidazole-based nanocarriers loaded with Moxifloxacin and Sulfamethoxazole showed enhanced bactericidal effects against multiple-drug-resistant bacteria compared with drugs alone, without affecting human cells. Our findings show that drug-loaded nanocarriers hold promise as potent chemotherapeutic drugs against multiple-drug-resistant bacteria.